Assembling, simulating, and recording robot videos as an effort to motivate middle school students and teachers of Science in Bengkulu Province - Mayub, Afrizal; Fahmizal, Fahmizal; Firdaus, M. Lutfi; Johan, Henny; Ruyani, Aceng; Karyadi, Bhakti (Institute of Advanced Engineering and Science, 2023)
The aim of this study was to determine the motivation of science teachers and students towards science after participating in the activity of assembling, simulating, and recording line follower robots as an effort to motivate middle school students and teachers towards science in Bengkulu Province. The research was done by direct practicing, where 60 students and 15 teachers of three junior high school (SMP): SMP Negeri 06 Seluma, SMP Negeri 02 Kota Bengkulu, and SMP Negeri 8 Rejang Lebong, were involved as the research subjects. The research activity concluded that the schools are ready to prepare simple electronics/robot laboratories for the three research subjects and the science teachers and students were motivated to learn science. It was seen from the score of 3.95 (scale of 1 to 5) for students, and for the science teacher, the score was 3.83 (scale of 1 to 5). The science teachers will follow up on robotics activities so that students will be interested in learning science at home and school.